ANALISIS PENGARUH PERUBAHAN HARGA TERHADAP VOLUME PENJUALAN PERTAMINA DEX SPBU CANGKRING DEMAK - Herri Wijaya; Ahmad Farid (JURNAL BISNIS DIGITAL DAN SISTEM INFORMASI, 2023)
Pertamina Dex's sales volume is obtained by gas stations from selling a number of liters of this fuel product at a predetermined price. By calculation, the sales result is the multiplication of the sales quantity with the selling price of oil per liter. Based on this, it is argued that there are two factors that affect sales volume, namely the selling price per liter and sales volume. The results of the variable regression coefficient of price changes are 6.087 for Pertamina Dex fuel products. That is, each price increases by Rp. 1 will increase the sales volume of 6,087 liters of Pertamina Dex products. The coefficient of determination (R2) is 0.004 for Pertamina Dex products. That is, for Pertamina Dex products, 0.4% of sales volume explains the product price change variable. From the regression coefficient on the t-count value is 0.2 for Pertamina Dex BBM products, less than the 5% t-table value of 2.23 so accept H0. The hypothesis of a change in price per liter of product affects the volume of product sales at the Cangkring Demak gas station, which places confidence at 95%. The frequent changes in the selling price of Pertamina Dex fuel at gas stations are too much influenced by the factor that world oil prices have increased but it doesn't matter that interest in Pertamina Dex fuel is still high.